Pulling force analysis in injection pultrusion of glass/epoxy composites. Issue 15 (18th November 2022) - Tucci, Fausto; Larrea-Wachtendorff, Dominique; Ferrari, Giovanna; Carlone, Pierpaolo
ABSTRACT: The present article studies the resistance opposed to the pulling force in injection pultrusion processes and its dependence on polymerization of the resin. A methodology to evaluate and analyze the local resistance to the advancement of the composite is proposed. Injection pultrusion processes were conducted adopting four different advancing speeds, equal to 100, 140, 180, and 220 mm/min. The interaction of the traveling material with the die has been analyzed and discussed referring to the temperature distribution and resin transitions evaluated by a finite element model. Numerical and experimental outcomes highlighted that the kinetic and rheological aspects in pultrusion are strictly dependent on the advancing velocity. Higher speeds determine an increase of the resistant force and reduction in the final degree of cure of the resin system. Detrimental effects on the quality of profiles pultruded at higher speed are demonstrated as well.